Performance and Intestinal Condition of Broiler Chicken with Various Body Weight at Hatch when Subjected to Fasting Post-hatch - B. Syamsuriadi; . Hamsah; S. Banong; W. Pakiding; M. R. Hakim (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
The research was aimed to determine the performance and intestinal condition of broiler chickens with various body weights (BW) at hatch when subjected to fasting post-hatch. Two hundred and sixteen broiler chickens Cobb aged 12 hours post-hatch and unsexed, were randomly assigned into floor pen, in which each pen filled with six chicks. The research was conducted in a factorial arrangement (3x4) according to completely randomized design with three replications for each treatment combination. The first factor was the BW at hatch i.e. light ((30.1±0.39g), medium ((33.3±0.44g), and heavy (33.3±0.44g). The second factor was the duration of fasting post-hatch (i.e. 24, 36, 48, and 60 h, respectively). Chickens respond on fasting treatment were observed on performance parameters (i.e. feed intake, growth rate, and feed conversion ratio), and intestinal dimension. Heavier chicks at hatch grew better and reached heavier final BW than smaller chicks, and were not influenced by fasting post-hatch. Fasting the chicks more than 48 h post-hatch, reduced the feed intake, retarded the growth, and had smaller intestine during the realimentation period, and these effects were maintained till the end of the experiment. The results of the study revealed that better performance of broiler chickens were achieved when the chicks accessed the feed no longer than 48 h post-hatch.